Assessment of Sexual Dysfunction in Patients with Fibromyalgia Syndrome - Rahime Nur Ülker; Tuncay Çakır; Soner Yalçınkaya; Ümit Seçil Demirdal; Naciye Füsun Toraman (Galenos Yayinevi, 2013)
Objectives: The aim of our study is to determine the presence, quality of sexual dysfunction in patients with fibromyalgia syndrome and to compare with normal population. Material and Methods: A total of 55 sexually active women who were admitted to Department of Physical Therapy and Rehabilitation of Antalya Research and Training Hospital and diagnosed with fibromyalgia syndrome according to 1990 and 2010 American College of Rheumatology (ACR) criteria. A control group composed of 50 sexually active women who were admitted to our clinic with various musculoskeletal system complaints were also included in the study in order to compare the parameters used for clinical assessment of patients and to determine whether the patients differ from normal population. Patients and controls who met inclusion criteria were applied Female Sexual Function Index (FSFI) for assessment of sexual function. This test was developed by Rosen and colleagues in 2000, it is composed of 19 questions and inquires six different dimensions including desire, arousal, lubrication, orgasm, sexual satisfaction and pain. Turkish validation test was done by Turkish Society Of Andrology in 2003, answers are multiplied with a coefficient and each section is evaluated on six scores. Minimum score is 2.4 and maximum is 36 and standardly used for assessment of female sexual dysfunction in Turkey. Results: Subscale and total score of Female Sexual Function Index of Fibromyalgia syndrome patients were found statistically significantly lower than those of control group (p<0.05). Conclusion: Disorders of sexual function or its quality are one of the problems seen in fibromyalgia syndrome patients. It should be noticed that sexual function assessment must be a part of treatment of fibromyalgia syndrome. It is quite difficult to determine the mechanism between sexual dysfunction and fibromyalgia syndrome and new and larger studies are needed to determine this mechanism. (Turkish Journal of Osteoporosis 2013;19: 65-8)